2020
DOI: 10.1093/geront/gnaa055
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Friendship Experiences and Cognitive Functioning in Later Life: The Mediating Roles of Adult Social Disconnectedness and Adult Loneliness

Abstract: Background and Objectives This study investigated the relationship between childhood friendships and cognitive functioning, as assessed with cognitive status and decline among adults aged 45 and older in China. We also examined the mediating effect of adult social disconnectedness and adult loneliness for this relationship. Research Design and Methods This study was based on 3 waves of data from the China Health and Retiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…These findings support the first hypothesis. In line with previous literature, the current study supported a life course perspective that childhood experiences have long-lasting implications for cognitive function (Burr et al, 2020;Chapko et al, 2017;Zahodne et al, 2019;Zhang et al, 2016Zhang et al, , 2018Zhang et al, , 2019Zhang et al, , 2020. Experiencing higher quality relationships with parents during childhood is posited to stimulate active lifestyles and positive attitudes toward education and skill development, improving coping skills when encountering stressful situations, and resulting in more motivation to engage in challenging cognitive tasks and activities.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings support the first hypothesis. In line with previous literature, the current study supported a life course perspective that childhood experiences have long-lasting implications for cognitive function (Burr et al, 2020;Chapko et al, 2017;Zahodne et al, 2019;Zhang et al, 2016Zhang et al, , 2018Zhang et al, , 2019Zhang et al, , 2020. Experiencing higher quality relationships with parents during childhood is posited to stimulate active lifestyles and positive attitudes toward education and skill development, improving coping skills when encountering stressful situations, and resulting in more motivation to engage in challenging cognitive tasks and activities.…”
Section: Discussionsupporting
confidence: 87%
“…For example, a study by Zahodne et al (2019) supported the thesis that greater childhood social support was related to better episodic memory in older Americans. Further, Burr et al (2020) found that Chinese older adults who retrospectively reported adverse friendship experiences in childhood exhibited worse baseline cognitive function and faster cognitive decline.…”
Section: Early Child-parent Relationship Quality and Later Life Cognitive Functionmentioning
confidence: 99%
“…Similarly, childhood interactions with friends and peers might help to stimulate cognitive development, and such social skills laid foundations for adulthood social relations, therefore possibly preventing social isolation and promoting cognitive maintenance in later life. By contrast, feelings of loneliness might lead to social disconnectedness and decrease levels of cognitive functioning in later life (Burr et al, 2020; Lempinen et al, 2018). Our results echoed the life course perspective and suggested that ACEs were critical to long-term individual health development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has linked childhood experiences with cognitive function in later life. For example, older adults are at a lower risk of cognitive impairment if they had better childhood friendship experiences ( 7 ). Additionally, childhood family-life happiness significantly predicts older adult cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that childhood friendship is significantly related to better cognitive function and slower cognitive decline in middle and old age ( 7 ). The cognitive reserve hypothesis postulates that participation in stimulating activities early in life can help the brain build a reserve to buffer against cognitive decline ( 14 ).…”
Section: Introductionmentioning
confidence: 99%